Penggunaan Media Pembelajaran Pada Mata Pelajaran Aqidah Akhlak - Rahmawati; Fatmawati; Mikyal Hardiyati (Pendidikan Guru Madrasah Ibtidaiyah, Universitas Nahdlatul Ulama Purwokerto, 2025)
This study aims to describe the use of learning media in the subject of Moral Faith in MIN 3 Hulu Sungai Selatan and its impact on the student learning process. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects include teachers of Moral Faith and students of MIN 3 Hulu Sungai Selatan. The results of the study show that the learning media used varies, including visual media, digital media, and traditional media. The use of these media is able to help students understand abstract concepts more concretely, increase learning motivation, instill moral values, and encourage students' activeness and critical thinking skills. Some of the obstacles in the use of media include limited facilities, lack of technology training for teachers, limited preparation time, and unstable internet networks.